DEVELOPMENT OF TECHNOLOGIES AND INNOVATIONS IN A MODERN UNIVERSITY: INTERNATIONAL MULTI-DISCIPLINARY STUDENT TEAMS SOLVING REAL PROBLEMS FOR INDUSTRY - Ph. A. Sanger (Высшее образование в России)
The industry/business community is demanding graduates who can perform in a real world environment. Industry-derived student projects provide a unique learning opportunity that makes the student’s technical knowledge relevant to real problems. International projects where students must work with students from different cultures add the many issues of culture and communication that real global team must face. This paper describes a proven model for incorporating these projects into a university curriculum and merits being at the core of University 3.0.